Metazoários endoparasitos da corvina Plagioscion squamosissimus (Heckel, 1840) dos rios Madeira e Negro da bacia Amazônica - Mendes, Priscilla Balestrin (2014)
The richness and diversity of Neotropical fish fauna is the world's largest, with about 4,500 described species. The Amazon basin is formed by all the rivers, streams and other water sources that flow into the Amazon River, the largest basin in the world. It is also considered the richest and most diverse freshwater fish in the world. Science metrics is the study of the quantitative aspects of science as a discipline or economic activity. It is applied in the development of science policy involves quantitative and scientific activities, including publishing studies. With the increase of available literature, this new tool has been widely used to try to understand the real meaning of the studies in various areas of scientific knowledge. Therefore, the first article aimed to make a science metric study of the parasites of fishes of the Amazon basin. The Amazon River has many tributaries, most importantly the left margin is the Rio Negro, characterized by having black waters. The right margin is the wood, a wide river and unlike the Black River is classified as white water. Plagioscion squamosissimus commonly known as "corvina" is a native fish of the Amazon basin and has great commercial and economic interest due to the appreciation of its delicate white flesh, which is considered an important part of the livelihood of local fishermen. Due to the peculiarities of the aquatic environment, such as the ease of propagation, fish exhibit high rates of infestation and infection by parasites. The host-parasite system represents a very peculiar model for ecological studies, it ensures the occupation of two classes of ecosystems by parasites. One is the host (biotic environment) itself and the other is the geographical area (abiotic environment) where the host population is located. Thus, each sample in a host population is a fragmented habitat comprising hierarchically structured parasitic communities. Such habitats are a natural replica relative to another host, allowing excellent opportunities for studies involving comparative analyzes of variability in community structures at all levels. Therefore, research related to ictioparasitologia are of great importance because the parasites can cause much harm to their hosts in addition to, most are species unknown to science. Related to knowledge of the parasitic fauna and host-parasite relationship studies are needed due to the economic importance of these fish species present for the region and for fish farming. With this, the second article was aimed at analyzing the endoparasite fauna of P. squamosissimus listed on the Madeira and Negro rivers of the Amazon basin, in the month of February 2012.